Sustainable Development of Agriculture: Modeling of Strategic Management in Transition Countries - Nadiia, Reznik; Anatoliy, Ostapchuk; Kateryna, Koshchenko (FEB - Universitas Lampung, 2019)
The aim of the paper is to provide a new view on the practice of concept development and the implementation of strategic management in the context of the return of some agricultural enterprises to the principles of a planned economy. Lack of research on this direction makes a topic of the paper is promising for consideration. This paper provides evidence-based explanations of the problem. As a result of research followed steps were made: the components of the algorithm of actions for the main executor of the strategy are singled out; the scheme of realization of strategic planning is offered; a list of predictive calculations has been compiled, which underlie modeling of the main directions of the industry development and are necessary for forecasting the development of agriculture; the criteria and principles of sustainable regional development have been determined and a scheme for its implementation has been developed.